2007
DOI: 10.3346/jkms.2007.22.1.94
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Circulating Vascular Endothelial Growth Factor and Soluble Flt-1 in Pregnancies Complicated by Preeclampsia

Abstract: To evaluate the role of vascular endothelial growth factor (VEGF) in the pathogenesis of preeclampsia, we measured total VEGF, free VEGF and soluble Flt-1 (sFlt-1) concentrations and determined their relationships. Maternal serum samples were collected from 20 patients with preeclampsia and 20 normotensive women with uncomplicated pregnancies matched with the patients with preeclampsia for gestational age and parity. The serum concentrations of total VEGF (2.39±0.75 vs. 0.28±0.14) and sFlt-1 (934.5±235.5 vs. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 26 publications
3
36
0
3
Order By: Relevance
“…A similar decrease in free maternal VEGF levels has also been reported by others. 8,31 It has been suggested that VEGF is responsible for the adequate perfusion of the feto-placental unit, normal fetal oxygenation, nutrition and appropriate intrauterine fetal growth; 9 the reduced VEGF levels observed in our study are similar to those found in other studies. [6][7][8][9] Reduced PlGF levels have been suggested to be a result of inadequate placental production, 12 which has been previously reported.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A similar decrease in free maternal VEGF levels has also been reported by others. 8,31 It has been suggested that VEGF is responsible for the adequate perfusion of the feto-placental unit, normal fetal oxygenation, nutrition and appropriate intrauterine fetal growth; 9 the reduced VEGF levels observed in our study are similar to those found in other studies. [6][7][8][9] Reduced PlGF levels have been suggested to be a result of inadequate placental production, 12 which has been previously reported.…”
Section: Discussionsupporting
confidence: 82%
“…8,31 It has been suggested that VEGF is responsible for the adequate perfusion of the feto-placental unit, normal fetal oxygenation, nutrition and appropriate intrauterine fetal growth; 9 the reduced VEGF levels observed in our study are similar to those found in other studies. [6][7][8][9] Reduced PlGF levels have been suggested to be a result of inadequate placental production, 12 which has been previously reported. 7,32 Qazi et al 33 have examined the circulating levels of VEGF and sFlt-1 and suggested that decreased VEGF levels resulting from elevated sFlt-1 might be a potential cause of the pathogenesis of preeclampsia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Besides angiogenesis, VEGF is believed to increase microvascular permeability and also promote coagulation in PIH disorders. 22 Several studies have demonstrated significantly elevated circulating VEGF concentration in women with PE; 23 however; recent studies have demonstrated decreased biologically active free VEGF concentrations in women with PE. 24 In this study, we observed that there was no change in VEGF levels in the complete control group, early weeks of GH and PE group, but these free VEGF levels were significantly elevated in late GH (P ¼ 0.0001), late PE (P ¼ 0.0001) and early (P ¼ 0.0001) and late (P ¼ 0.0001) eclampsia pregnant groups as compared with the control group, suggesting altered VEGF concentrations according to severity of these disorders.…”
Section: Discussionmentioning
confidence: 99%